Particulate matter emission from bio-oil incomplete combustion under conditions relevant to stationary applications - Feng, C.; Gao, X.; Wu, Hongwei (2016)
© 2015 Elsevier Ltd. All rights reserved. A raw bio-oil from biomass fast pyrolysis and a filtrated bio-oil, which was prepared from the raw bio-oil via syringe filtration to remove fine char particles, were atomized via an air-assist nozzle set and then combusted in a laboratory-scale drop-tube furnace (DTF) at 1400 °C under incomplete combustion conditions. Both air and oxygen (O2) atmospheres were considered to produce PM with aerodynamic diameter of <10 µm (PM10). Regardless of experimental conditions, it was found that the particle size distributions (PSDs) of PM10 follow a bimodal distribution. Under such incomplete combustion conditions, the PM10 samples apparently contain substantial amounts of carbonaceous material. Whereas the PSDs of Na, K, Cl and S (in the form of SO42-) exhibit a unimodal distribution, those of Mg and Ca in PM10 are dependent on combustion atmosphere, i.e. a unimodal distribution for air combustion and a bimodal distribution for O2 combustion. The results show that under incomplete combustion conditions, the fine char particles in the raw bio-oil play significant roles in the emission of PM10 as well as Mg and Ca in PM10. The removal of the fine char particles in the raw bio-oil leads to considerable reductions in the mass of PM with aerodynamic diameters of 0.1-10 µm as well as that of Mg and Ca in the PM with a size range of 0.372-10 µm from the filtrated bio-oil combustion, compared to those from the raw bio-oil combustion. Combustion atmospheres also have significant effects on the emission and chemical composition of PM10 due to incomplete combustion. Switching combustion atmosphere from air to O2 increases the PM1 yield by ~74.2% due to the increased yields of Na, K, Mg, Ca, SO42- and PO43- in PM1, but decreases the PM1-10 yield by ~27.2%, apparently as a result of improved burnout and thereby decreased amounts of unburned carbonaceous material in PM1-10.